THE SUFISM IN AZERBAIJAN AND SAFAVIYYA ORDER (TARIQA) - Gubadov, Gadim (Scientific Journal of Polonia University, 2023)
Sufism was one of the main trends of ideas in the XI-XII centuries. Until the 11th century, the activities of Sufi thinkers, the direction of their ideas, along with the economic and social-political conditions, mainly determined their individual ways of life. From the end of the 10th century, Sufi communities were organized and began to spread widely. Individual sheikhs gathered many murids around them, and prepared their future followers according to the strict rituals they designed for them. The purpose of the article is to reveal that Azerbaijan is a Sufi spiritual and moral center. In the Middle Ages, as everywhere in the Islamic world, influential sheikhs grew up in Azerbaijan, and many Sufi spiritual and moral centers – sects (tariqas) were founded. One such sect was “Safawiyyah” founded by Sheikh Safiaddin Ardabili in the 13th century, which gained influence in a short period of time and gathered many disciples around it. “Safawiyya” sect has been under the influence of various ideas and Sufi currents since its inception. Among those Sufi teachings, the tradition of the “Suhrawardiyya” order is famous for playing an important role in the formation of “Safawiyya”. In this regard, the name of another sect should be mentioned.